Aquatic toxicity, bioaccumulation potential, and human estrogen/androgen activity of three oxo-Liquid Organic Hydrogen Carrier (oxo-LOHC) systems - Seol, Yohan; Markiewicz, Marta; Beil, Stephan; Schubert, Sara; Jungmann, Dirk; Wasserscheid, Peter; Stolte, Stefan (Journal of Hazardous Materials, 2024)
The Liquid Organic Hydrogen Carrier (LOHC) technology offers a technically attractive way for hydrogen storage. If LOHC systems were to fully replace liquid fossil fuels, they would need to be handled at the multi-million tonne scale. To date, LOHC systems on the market based on toluene or benzyltoluene still offer potential for improvements. Thus, it is of great interest to investigate potential LOHCs that promise better performance and environmental/human hazard profiles. In this context, we investigated the acute aquatic toxicity of oxygen-containing LOHC (oxo-LOHC) systems. Toxic Ratio (TR) values of oxo-LOHC compounds classify them baseline toxicants (0.1 < TR < 10). Additionally, the mixture toxicity test conducted with D. magna suggests that the overall toxicity of a benzophenone-based system can be accurately predicted using a concentration addition model. The estimation of bioconcentration factors (BCF) through the use of the membrane-water partition coefficient indicates that oxo-LOHCs are unlikely to be bioaccumulative (BCF < 2000). None of the oxo-LOHC compounds exhibited hormonal disrupting activities at the tested concentration of 2 mg/L in yeast-based reporter gene assays. Therefore, the oxo-LOHC systems seem to pose a low level of hazard and deserve more attention in ongoing studies searching for the best hydrogen storage technologies.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Bioconcentration factor; Ecotoxicity; Emerging pollutants; Hydrogen storage; Yeast-based reporter gene assay